Penggunaan Media Permainan Ludo Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VII SMP Trinitas Lorwembun - Yesica Emelda Duarmas; Yoseph Batkunde; Zakarias Bacori (Mandalika Mathematics and Educations Journal, 2022)
Mathematics is a science that is essentially abstract. Mathematics is also a science that has regular patterns related to ideas, processes, and reasoning. Learning media is anything that can be used to convey messages or information in the teaching and learning process so that it can stimulate students' attention and interest in learning. The type of research used in this research is quantitative research with a descriptive approach. Quantitative research method is one type of research whose specifications are systematic, well-planned and clearly structured from the beginning to the making of the research design. The subjects of this study were the seventh grade students, totaling 16 students. This research was carried out in 4 meetings, namely as follows: (1) the process of implementing the initial test, (2) the process of implementing the first learning, (3) the second learning process, (4) the process of implementing the formative test. Quantitative data in the form of student learning outcomes obtained through tests. The results showed that there was an increase in the line and angle material for class VII Trinitas Lorwembun Junior High School using the Ludo game mathematics learning media, namely 16 students with a percentage of 100% experiencing completeness in the learning process.